ANALISIS KESESUAIAN AKAD WADIAH YAD AL AMANAH PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BMT AL ITTIFAQIAH INDRALAYA - Darsi Ahmadan; Sufi Yanti; Hidayani; Hairunnisa (Program Studi Perbankan Syariah, 2024)
The results of this research can generally be concluded that the research that the author presents with these relevant data, after being processed andanalyzed, there are several important points relating to the implementation of wadiah contracts on deposits at BMT Al ittifaqiah, Indralaya, so the author concludes as follows: Savings products at BMT Al ittifaqiah use the wadi'ah contract, in this case the wadi'ah contract used is the wadi'ah yad amanah contract. This research aims to determine the implementation of the wadiah contract at BMT Al-ittifaqiah, the suitability of financing the wadiah contract at BMT Alittifaqiah. The type of research carried out in this research is field research, while the type of data is qualitative data. Qualitative data is data that shows the quality or qualities of something that exists, whether circumstances, processes, events or occurrences and others which are expressed in the form of statements or in the form of words